Patterns identification in the dynamics of countries’ technological development in the context of military conflict - Prokopenko, Olha; Bezliudnyi, Oleksandr; Omelyanenko, Vitaliy; Slatvinskyi, Maksym; Biloshkurska, Nataliia; Biloshkurskyi, Mykola (Eastern-European Journal of Enterprise Technologies, 2021)
A comparative assessment of the dynamics of technological development of Ukraine and Russia for 2014–2019 has been carried out in the context of the Russian-Ukrainian war. A method for assessing the economic losses of the conflicting parties due to a slowdown in their technological development, under the influence of militarization, based on the parameter of technological progress of the Solow-Tinbergen production function, built according to the World Bank 1991–2019 data, was proposed and tested. It is substantiated that during the Russian-Ukrainian war, starting from 2015, the technological development of the Russian Federation was curtailed and the economy transitioned to an extensive basis, when the parameter of technological progress acquired a negative value. In the case of Ukraine, a deterioration in technological development was detected due to a decrease in the values of the parameter of technological progress during 2014–2019. It has been proven that the economic recession of the aggressor is the worst in comparison with the victim country, but the relative losses of GDP due to the curtailment of technological development caused by the war are much less. In the case of the Russian Federation as an aggressor country, it is substantiated that the main catalyst for the economic recession was the curtailment of the participation of the real sector of the economy in the international transfer of technologies under the influence of international economic sanctions. In the case of Ukraine, as a country-victim of military intervention, it is justified that the replacement of international partnership in the field of technological cooperation ensured a slowdown in the economic recession. The results of the development of methodological support for the process of assessing GDP losses of the parties to a military conflict are universal for use in international comparisons. The proposed methods are relevant in assessing the technological development of countries that are or were in a state of military confrontation, which significantly expands the basis for future research by the authors